Pesticide Toxicity Profile: Miscellaneous Rodenticides - Frederick M. Fishel (EDIS, 2005)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross reference of chemical, common and trade names of miscellaneous rodenticides registered for use in Florida. This document is PI-78, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 2005.